A retrospective observational study to evaluate the clinical outcomes and routine management of patients with chronic lymphocytic leukaemia treated with idelalisib and rituximab in the UK and Ireland (RETRO‐idel). (14th June 2021) - Eyre, Toby A.; Preston, Gavin; Kagdi, Huseini; Islam, Amin; Nicholson, Toby; Smith, Harry W.; Cursley, Adam P.; Ramroth, Heribert; Xing, Guan; Gu, Lin; Rajakumaraswamy, Nishanthan; Fegan, Christopher
Summary: Idelalisib (IDL) is an oral first‐in‐class phosphatidylinositol 3‐kinase delta (PI3Kδ) inhibitor approved for chronic lymphocytic leukaemia (CLL) alongside rituximab (R) since 2014. However, little data exist on routine practice. The RETRO‐idel was a protocol‐led, retrospective study of 110 patients [ n  = 27 front‐line (1L)] who received IDL‐R. The primary end‐point was clinical overall response rate (ORR). The median (range) follow‐up of the whole cohort was 30·2 (0·1–51·9) months. The median (range) age was 72 (48–89) years. Tumour protein p53‐disruption was common [100% 1L, 32·5% relapsed/refractory (R/R)]. The best ORR (intention‐to‐treat) was 88·2% (1L 96·3%, R/R 85·5%). Overall, the median event‐free survival (mEFS) was 20·3 months and time‐to‐next treatment was 29·2 months. The mEFS for 1L patients was 18·7 months and R/R patients was 21·7 months. The 3‐year overall survival was 56·1% (95% confidence interval 45·7–65·3). IDL was discontinued in 87·3% ( n  = 96). More patients discontinued due to adverse events in the front‐line setting (1L 63·0% vs. R/R 44·6%) and due to progressive disease in R/R patients (20·5% vs. 3·7% in 1L). Lower respiratory tract infection/pneumonia were reported in 34·5% (Grade ≥3, 19·1%), diarrhoea in 30·9% (Grade ≥3, 6·4%), and colitis in 9·1% (Grade ≥3, 5·5%). Overall, these data describe clear efficacy for IDL‐R in routine practice. No new safety signals were identified, although careful management of known toxicities is required.